(untitled) (Muqarin Review: Jurnal Perbandingan Mazhab, 2024)
This study aims to describe the dynamics of the development of press freedom policies in Indonesia, until the issuance of Law Number 40 of 1999 concerning the Press which became the legal basis for press freedom in Indonesia. Indonesia. In practice, the freedom of the press that applies in Indonesia is not absolute freedom. But this freedom of the press must be supported by responsibility and ethics to create an ideal world of the press. To form an ideal press, journalists must put forward a journalism code of ethics as the basis of ethics and uphold the norms that apply in society so as not to harm other parties. although there are ethical restrictions on press freedom, these restrictions do not curb press freedom but are created as a means to respect everyone’s freedom and aim for the common good, this is in line with the concept of Islamic religious norms to achieve maqasid sharia, namely the goal of establishing law for the benefit of maintaining rights -Rights are human needs. The results of the research show that press freedom in Indonesia is not liberal. However, freedom of the press must be guided by press regulations as stated in the press law and journalistic code of ethics which also accommodate the values contained in Islamic religious norms contained in the Al-Quran and Sunnah.